The Association of Risk Factors and Severity of Acute Coronary Syndrome with Serum Uric Acid Levels in Female Population Younger Than 45 Years (Medical Forum Monthly, 2021)
: The study aimed to evaluate Uric Acid levels in the female population younger than 45 years and to demonstrate if its levels are correlated with severity and risk factors of Coronary Artery disease in Acute Coronary Syndrome patients.Study Design: A Cross-sectional analytical studyPlace and Duration of Study: This study was conducted at the Cardiology ward of Ch.Pervaiz Elahi Institute of Cardiology Multan from July 2020 to Dec 2020 for a period of six months.Materials and Methods: A total of 60 women aged less than 65 years old were included in the study following inclusion and exclusion criteria. Patients were evaluated for their family history and coronary artery risk factors such as hypertension, diabetes, dyslipidemia, family history, smoking, and body mass index. Blood samples were collected for evaluation of serum uric acid and two groups were formed: hyperuricemia and non-hyperuricemia. Coronary angiography was performed to determine the number of coronary arteries involved. Each risk factor and extent of severity of disease was compared for mean serum uric acid level between two groups. Statistical analysis was conducted on SPSS using version 23.Results: Among analyzed 60 female patients, 31% had STEMI, 48% were diagnosed with NSTEMI, and 21% had unstable angina. 75% of patients were aged between 30-45 years. Among risk factors, hypertension (mean value=7.55± 1.72), diabetes (7.62±2.13), and dyslipidemia (7.77±1.78) were found to be significantly associated with hyperuricemia. Similarly, the higher number of involved coronary arteries was significantly related to higher uric acid levels (p=0.0001).Conclusion: Shortly, serum UA is correlated with risk factors of coronary artery disease (CAD) like diabetes, hypertension, and dyslipidemia in the young female population. Similarly, it is a significant predictor of the severity of Coronary artery disease.